ANALISIS KINERJA KEUANGAN PEMERINTAH DAERAH KOTA SEMARANG SEBELUM DAN SAAT PANDEMI COVID-19 - Nisfi Nova Karina; Puji Wibowo (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2022)
Analysis of the financial performance of local governments is one of the tools that can be used to evaluate the financial performance of LKPD as a basis for decision making. This study aims to analyze the financial performance of the Semarang City Government using 5 financial ratios. The data used is secondary data, in the form of local government budget (APBD) data for the 2018-2021 fiscal year. The ratio of analysis used consists of the degree of fiscal autonomy, the ratio of independence, the ratio of effectiveness of PAD, the efficiency ratio, and the ratio of compatibility. The results showed that in general, the financial performance of the Semarang City Government was quite good even though during the pandemic there was a decline. This can be seen from the positive growth of DOF, the ratio of independence to the pattern of consultative relations, the effectiveness of PAD is quite effective, the financial efficiency of the region is quite efficient, and the ratio of direct expenditure and indirect expenditure compatibility is very good